A quest for teacher leadership in the twenty-first century – emerging themes for future research. Issue 2 (20th September 2019) - Wang, Mo; Ho, Dora
Abstract : Purpose: The purpose of this paper is to provide a research synthesis of findings drawn from studies of teacher leadership published in English-based journals from 2000 to 2018. The goal of the research synthesis was to develop new insights into teacher leadership through a theoretical discussion and to identify emerging themes for future research. Design/methodology/approach: The methodology employed in this study was systematic review. The study first identifies a body of relevant literature and research on teacher leadership from the English-based journals from 2000 to 2018. Information concerning the nature of the studies as well as substantive findings was extracted from each of the articles. Synthesis of findings was accomplished by identifying key themes in the literature. Findings: The synthesis yielded four themes: "the notion of teacher leadership, " "the theoretical perspectives are used for understanding teacher leadership, " "the factors are influencing the development of teacher leadership, " and "the approach to build and develop leadership capacity." Originality/value: This paper attempts to offer a critical review on the current literature and research on teacher leadership, reveal if there are any gaps in the ongoing debate, and identify the agenda for future research. This paper not only explores "what there is, " but also examines "what is missing, " and "what could be improved upon" by reviewing research findings that emerged in the teacher leadership literature produced from 2000 to 2018. The paper could shed light on the existing research about teacher leadership.